Los nuevos aranceles implantados a los televisores pantalla plana, y los cupos que la aduana impone para el ingreso de celulares y vehículos nuevos en el año 2012 sus causas y efectos en nuestra economía y el impacto que producen en los importadores y consumidores en la ciudad de Quito. - Mora Recalde, Andrés Ernesto (2014)
Our research has been collecting information on the impact that caused the limiting measures in units imports vehicles, cellular and increased tariffs on TVs, importers of cars, televisions and cell have seen their sales decrease with the limiting measures, these have caused that there is a shortage of the aforementioned goods and to adjust properly their prices have had to reduce their profitability to capture the customer's attention and not decrease their market share, negative effects have been increasing with time lag far only in the first year of implementation of the limiting measure in the automotive sector, 63% of importers has reduced 30% of imports in the marketing of appliances such as the televisions, 19% of importers been reduced by 30% on imported units and finally 58% of the population importers cell phones have reduced by 30% of its imports.